Y / 4Z = X / W
==> cross multiply
4ZX = YW
==> divide by 4X
Z = YW / 4X
That's your answer: Z = YW / 4X
2007-06-28 10:09:47
·
answer #1
·
answered by C-Wryte 3
·
0⤊
0⤋
Here is your problem
y/4z=x/w
First,we've to make a domain so that the equation remains true always.
'z' & 'w' can not have a value zero for they are denominators,else the equation will be undefined.
By cross multiplying the equation,we get:
4xz=wy
Dividing both sides by 4x,we'll get:
z=1/4(wy/x); 'x' is different from zero
2007-06-28 17:19:53
·
answer #2
·
answered by myfateismydestiny 1
·
0⤊
0⤋
Y / (4Z) = X / W
cross multiply => YW = 4XZ
divide both sides by 4X => YW / (4X) = Z
or Z = (WY) / (4X)
2007-06-28 17:15:00
·
answer #3
·
answered by Feb 3
·
0⤊
0⤋
You're notation is a bit confusing, but if I'm reading it correctly, it goes:
y / (4z) = x / w
y = (x4z) / w
z = (w y ) / (x4)
2007-06-28 17:10:02
·
answer #4
·
answered by Erin G 2
·
0⤊
0⤋
I have to spell it out:
Z equals x over w times 1 over y, with all of that over 4.
Hope that makes sense!
2007-06-28 17:17:09
·
answer #5
·
answered by Kevin 1
·
0⤊
0⤋
same as 4Z/Y = W/ X, so
4Z = WY/X, and
Z = WY/4X
2007-06-28 17:10:30
·
answer #6
·
answered by John V 6
·
0⤊
0⤋
WY=4ZX
WY/4X=Z
treat yourself
2007-06-28 17:11:13
·
answer #7
·
answered by mking785 2
·
0⤊
0⤋
y/4z = x/w
yw = 4xz
z = (yw)/(4x)
2007-06-28 17:10:48
·
answer #8
·
answered by Azshira 3
·
0⤊
0⤋
W Y = 4 X Z
Z = (WY) / (4X)
2007-07-02 11:39:03
·
answer #9
·
answered by Como 7
·
0⤊
0⤋